Using mark-recapture methods to estimate population size and survival of pyjama sharks Poroderma africanum in Mossel Bay, South Africa. Issue 4 (17th December 2019) - Grusd, SP; Moloney, CL; Distiller, G; Watson, RGA; Cowley, PD; Gennari, E
Abstract : The pyjama shark Poroderma africanum (family Scyliorhinidae) is endemic to coastal waters of South Africa but its population characteristics are poorly known. This study aims to estimate baseline demographic parameters for P. africanum in Mossel Bay. We applied mark-recapture methods following Pollock's robust design (PRD) and Cormack–Jolly–Seber (CJS) models, using five-year tag-recapture data and one-year acoustic-telemetry data, respectively. Estimates of abundance, survival, capture probabilities and temporary emigration were obtained using these models. The PRD model indicated random temporary emigration (0.955 period –1 [95% CI 0.755–0.993]), constant survival, and season-varying capture and recapture probabilities with a negative behavioural response to first capture (β = −5.34 [−6.89 to −3.80]). Abundance estimates ranged from 11 (10.01–13.21) to 53 (52.05–56.82) sharks in Mossel Bay. The CJS model indicated constant survival (0.271 y –1 [95% CI 0.0–0.75]) and sex-independent probabilities of being captured at least once annually (1.0 y –1 for both sexes). This study provides the first demographic information for the management of this population. Further studies should utilise larger sample sizes and more complex models, and investigate specific management options.